Evaluation of the hydrophobic and barrier properties of the polyurethane coatings covered by stearic acid thin layer - Nguyen, Anh Son; Nguyen, Thuy Duong; Pham, Thu Thuy; Vu, Ke Oanh; To, Thi Xuan Hang; Trinh, Lan Phuong; Dam, Xuan Thang; Bui, Minh Quy (Communications in Physics, 2023)
In this paper, a thin stearic acid (SA) film was deposited onto the polyurethane (PU) coatings with different concentrations of stearic acid in the ethanol (1 wt.%, 2 wt.% and 3 wt.%) by centrifuged technique. Fourier transform infrared spectra (FTIR) and water contact angle (WCA) method were performed to characterize and evaluate the hydrophobic layer formed on the surface of the samples. Then, the barrier property of the PU/SA was assessed by using electrochemical impedance spectroscopy (EIS) and accelerated salt spray test method. The results show that the presence of the stearic acid layer was effective for both hydrophobic and barrier properties, especially the samples prepared with 3 wt.% stearic acid. This work landmarks the need for improving the protection ability of polyurethane coatings for a metallic substrate.